e
x
=
1
+
x
1
!
+
x
2
2
!
+
⋯
+
x
n
n
!
+
ο
(
x
n
)
e^x=1+\displaystyle\frac{x}{1!}+\frac{x^2}{2!}+⋯+\frac{x^n}{n!}+\omicron(x^n)
ex=1+1!x+2!x2+⋯+n!xn+ο(xn)
ln
(
1
+
x
)
=
x
−
x
2
2
+
x
3
3
+
⋯
+
(
−
1
)
n
−
1
n
x
n
+
ο
(
x
n
)
\ln{(1+x)}=x-\displaystyle\frac{x^2}{2}+\frac{x^3}{3}+⋯+\frac{(-1)^{n-1}}{n}x^n+\omicron(x^n)
ln(1+x)=x−2x2+3x3+⋯+n(−1)n−1xn+ο(xn)
sin
x
=
x
−
x
3
3
!
+
x
5
5
!
+
⋯
+
(
−
1
)
n
(
2
n
+
1
)
!
x
2
n
+
1
+
ο
(
x
2
n
+
1
)
\sin x=x-\displaystyle\frac{x^3}{3!}+\frac{x^5}{5!}+⋯+\frac{(-1)^{n}}{(2n+1)!}x^{2n+1}+\omicron(x^{2n+1})
sinx=x−3!x3+5!x5+⋯+(2n+1)!(−1)nx2n+1+ο(x2n+1)
cos
x
=
1
−
x
2
2
!
+
x
4
4
!
+
⋯
+
(
−
1
)
n
(
2
n
)
!
x
2
n
+
ο
(
x
2
n
)
\cos x=1-\displaystyle\frac{x^2}{2!}+\frac{x^4}{4!}+⋯+\frac{(-1)^{n}}{(2n)!}x^{2n}+\omicron(x^{2n})
cosx=1−2!x2+4!x4+⋯+(2n)!(−1)nx2n+ο(x2n)
t
a
n
x
=
x
+
1
3
x
3
+
1
5
x
5
+
⋯
+
1
2
n
+
1
x
2
n
+
1
+
ο
(
x
2
n
+
1
)
tanx=x+\displaystyle\frac{1}{3}x^3+\frac{1}{5}x^5+\cdots+\frac{1}{2n+1}x^{2n+1}+\omicron(x^{2n+1})
tanx=x+31x3+51x5+⋯+2n+11x2n+1+ο(x2n+1)
推导:
(
tan
x
−
x
)
∼
1
3
x
3
∼
(
x
−
arctan
x
)
(
x
−
sin
x
)
∼
1
6
x
3
∼
(
arcsin
x
−
x
)
α
∼
β
⇒
α
=
β
+
ο
(
β
)
得
tan
x
=
x
+
1
3
x
3
+
ο
(
x
3
)
同理
arctan
x
,
arcsin
x
\begin{aligned} 推导:&(\tan x -x)\sim\displaystyle\frac{1}{3}x^3\sim(x-\arctan x)\\ &(x−\sin x) \sim\displaystyle\frac{1}{6}x^3 \sim (\arcsin x−x)\\ &\alpha \sim \beta \Rightarrow \alpha=\beta+\omicron(\beta)\\ &得\ \tan x=x+\displaystyle\frac{1}{3}x^3+\omicron(x^3)\\ &同理\ \arctan x,\arcsin x &&&&&&&&&&&&&&&&&&&&&&&&&&&&& \end{aligned}
推导:(tanx−x)∼31x3∼(x−arctanx)(x−sinx)∼61x3∼(arcsinx−x)α∼β⇒α=β+ο(β)得 tanx=x+31x3+ο(x3)同理 arctanx,arcsinx
1
1
−
x
=
1
+
x
+
x
2
+
⋯
+
ο
(
x
n
)
\displaystyle\frac{1}{1-x}=1+x+x^2+\cdots+\omicron(x^n)
1−x1=1+x+x2+⋯+ο(xn)
1
1
+
x
=
1
−
x
+
x
2
+
⋯
+
(
−
1
)
n
x
n
+
ο
(
x
n
)
\displaystyle\frac{1}{1+x}=1-x+x^2+\cdots+(-1)^nx^n+\omicron(x^n)
1+x1=1−x+x2+⋯+(−1)nxn+ο(xn)
(
1
+
x
)
a
=
1
+
a
1
!
x
+
a
(
a
−
1
)
2
!
x
2
+
⋯
+
a
(
a
−
1
)
⋯
(
a
−
n
+
1
)
n
!
x
n
+
ο
(
x
n
)
(1+x)^a=1+\displaystyle\frac{a}{1!}x+\frac{a(a-1)}{2!}x^2+\cdots+\frac{a(a-1)\cdots(a-n+1)}{n!}x^n+\omicron(x^n)
(1+x)a=1+1!ax+2!a(a−1)x2+⋯+n!a(a−1)⋯(a−n+1)xn+ο(xn)
arcsin
x
=
x
+
1
2
×
x
3
3
+
1
×
3
2
×
4
×
x
5
5
+
o
(
x
5
)
=
x
+
x
3
6
+
ο
(
x
3
)
\arcsin x=x+\displaystyle\frac{1}{2}\times\frac{x^3}{3}+\frac{1\times3}{2\times4}\times\frac{x^5}{5}+o(x^5)=x+\frac{x^3}{6}+\omicron(x^3)
arcsinx=x+21×3x3+2×41×3×5x5+o(x5)=x+6x3+ο(x3)
arctan
x
=
x
−
x
3
3
+
x
5
5
+
⋯
+
(
−
1
)
n
2
n
+
1
x
2
n
+
1
+
ο
(
x
2
n
+
1
)
\arctan x=x-\displaystyle\frac{x^3}{3}+\frac{x^5}{5}+⋯+\frac{(-1)^{n}}{2n+1}x^{2n+1}+\omicron(x^{2n+1})
arctanx=x−3x3+5x5+⋯+2n+1(−1)nx2n+1+ο(x2n+1)